RANCANG BANGUN ALAT UJI KUALITAS DENSITY BAHAN BAKAR MINYAK BERDASARKAN METODE TEKANAN HIDROSTATIS - Ardiansyah, Yul; Riza Alfita; Koko Joni; Haryanto (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2021)
The measurement of the quality of the density of fuel oil is one of the mandatory activities in the management of the fuel oil supply station (SPBU) business. Density quality test is Pertamina’s way to maintain the quality or standard of fuel that will be used by gas station producers. Measurement of the quality test of the standard density of fuel used at gas stations is conventional or manual measurement using a hydrometer and thermometer. In this final project, a design tool for quality fuel oil density test is made which is useful for maintaining the quality of Pertamina’s fuel when distributed to gas stations by using parameters of density and temperature. This research aims to produce a quality density test tool for fuel in accordance with the standard density set by Pertamina using the ATMEGA16 microcontroller-based hydrostatic pressure method and the Sturdy PC521 USB Webcam Camera as a detector for the height of a liquid and the MLX90614 sensor as a temperature detector. Because the parameters of this method can only be used in ideal conditions, to get the density according to the measurement standards of Pertamina, the combination value for Lux needed by the camera and the camera's viewing distance is with the light intensity 54-59 Lux with a webcam camera distance of 40cm facing the object (Fuel Oil). Output processing from the Sturdy PC521 Usb Webcam Camera and MLX90614 sensor will be displayed in the Delphi XE7 GUI.